(untitled) (Journal of Fiber Bioengineering and Informatics, 2019)
In view of the current situation that there exists big impact and friction between the gripper and the guide in the weft insertion mode of the existing gripper loom, this paper puts forward the idea of the electromagnetic-driven two-way weft insertion on gripper in order to improve the energy conversion efficiency, reduce the friction and mechanical vibration. Electromagnetic drive is used as the basic method to study the projecting/braking of the shuttle, and it uses the principle of electromagnetic levitation as the basic principle of the shuttle’s weft insertion. In this paper, a basic model of two-way insertion is established. After ANSYS simulation and experimental analysis, the speed of electromagnetic driving can reach 30 m/s. In the electromagnetic levitation stage, PWM modulator and DC power regulation were respectively used to conduct the levitation control experiment. HW101 hall sensor was used to judge the levitation state, and with the assistance of other Operational Amplifier, the requirements of electromagnetic levitation were completed.